The Competitiveness of Beef Cattle Business on Various Agro-Ecological Zones in Tegal Regency - Sugiarto, Moch; Wakhidati, Yusmi Nur; Einstein, Alief; Khaerudin, Khaerudin (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
The competitiveness of livestock business is one strategic issue to guarantee the empowerment and sustainability of small scale beef cattle business. The study conducted on the competitiveness of beef cattle business in Tegal regency aims at (1) identifying the competitiveness of beef cattle business in various agro-ecological zones and (2) analyzing factors influencing the business competitiveness. This study employs a survey method to 100 beef cattle farmers in Tegal Regency. The respondents are selected using a stratified random sampling technique based on the agro-ecological zones (highland, lowland, and coastal areas). The observed variables are business efficiency, farmers’ age, farmers’ education, farming experience, number of family members, and number of cattle. The data are processed using ANOVA and multiple linear regressions. The beef cattle business in Tegal Regency is quite competitive which is characterized with the business efficiency by 1.39. The beef cattle business at the highlands has a higher competitiveness than that at the other agro-ecological zones (P <0.01). The competitiveness of beef cattle business is influenced by the farmers’ age (P <0.05), as well as the farming experience and number of cattle (P <0.01). The development of beef cattle business scale accompanied by the development of livestock production technical ability should be made to strengthen the competitiveness of beef cattle business in Tegal regency.